Performance improvement of dye-sensitized solar cells with Ag nanoparticles - Shah, Shahan; Zainal Abidin, Zul Hazrin; M. Noor, I.; Osman, Zurina; Arof, A. K. (Taylor and Francis Group, 2023)
Light absorption by photovoltaic (PV) devices is shown to improve with the use of plasmonic silver nanoparticles (100 nm size) added to the active layer of dye-sensitized solar cell (DSSCs). The electrolyte containing 2 wt. silver nanoparticles exhibits the highest conductivity of 1.27 × 10−2 S cm−1. The DSSC using this electrolyte exhibits the highest efficiency of (6.99 ± 0.15) . The Jsc is (14.25 ± 0.71) mA cm−2, Voc is (0.70 ± 0.01) V and FF is (69.94 ± 3.80) . The same DSSC also exhibits the shortest electron transport time, τtr of (7.00 ± 0.41) ms and long recombination time, τrec of (87.22 ± 9.17) ms.